Marketing of coaches' distant improvement of professional skills - Petrova О.A; Tomashevskyy V.V (Kharkov National Pedagogical University, 2012)
By means of marketing researches influence of political, legal, economic, scientific and technical and socially-demographic factors on system of coaches' distant improvement of professional skills is analyzed. Estimations of 12 experts were used for the lead through of marketing «PETS»- analysis and constructions of matrix of «SWOT»-analysis. The expediency of introduction of system of Ukrainian coaches distant improvement of professional skills is defined, are revealed strong and weaknesses, threats and favorable possibilities of the given system for physical training and sports sphere in Ukraine. The influence of threatening factors almost in 2,5 times less than, than factors of favorable possibilities of development of the system of coaches' distant improvement of professional skills is set.